Re-Evaluating the Development of the Islamic Sciences: The Case Against the Classical Narrative and the Myth of Decline - Lucas, Adam (Unisia, 2024)
Eurocentric myths about Western scientific and technological superiority persist in popular culture and some scholarly circles. A prevalent myth suggests that Islamic contributions to modern science were primarily the transmission of ancient Greek and Roman knowledge to medieval and early modern Europe. A less extreme version posits significant contributions during Islam’s "Golden Age," followed by a decline between the late eleventh and late fourteenth centuries. This paper challenges these narratives, presenting recent scholarship that demonstrates continuous major advances in astronomy, physics, mathematics, and medicine by Islamic scholars throughout the late Middle Ages and into the early modern period. The study underscores the inadequacy of the classical narrative, which claims that Islamic scientific activity declined after an initial period of prosperity. Historians like Eugene von Grunebaum, Otto Neugebauer, and George Saliba have provided evidence that Islamic scholars not only preserved ancient knowledge but also made original contributions that influenced later European developments. This includes advancements in fields such as astronomy, where figures like Nasir al-Din al-Tusi and Ibn al-Shatir developed models later utilized by Copernicus. The paper also highlights continued progress in medicine and mathematics, with scholars like Al-Razi and Ibn Sina making lasting impacts on European scientific thought. The article argues for a re-evaluation of the role of Islamic sciences, emphasizing that many significant contributions remain understudied due to a lack of accessible manuscript sources. By debunking the myth of decline, the paper calls for recognition of the dynamic and sustained intellectual activity within Islamic cultures, which continued to produce influential scientific work well into the early modern era.